Między aktorstwem a histerią w filmie Andrzeja Żuławskiego "Na srebrnym globie" = Between Acting and Hysteria in Andrzej Żuławski`s Film "On the Silver Globe" - Prusinowski, Piotr (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Andrzej Żuławski`s unfinished film "On the Silver Globe" (1987), based on the so?called "luna trilogy" by his granduncle Jerzy Żuławski, remains exemplary for direktor`s distinctive aesthetics. Over?the?top "hysterical" acting reflects his delirious vision of the world. First and foremost, an artist directed viewer`s attention towards female characters who represent "point of view on the Word in his films" - they had to "show the whole spectrum of the human temperament".
Keywords: film polski; fantastyka naukowa; surrealizm; aktorstwo; filmowa adaptacja prozy młodopolskiej; Polish film; science fiction; surrealism; acting; film adaptation of literary work from the period of Young Poland